FEATURES OF DOMESTIC VIOLENCE IN THE FAMILY: STATE GUARANTEE FOR THE PROTECTION OF WOMEN AND GENDER EQUALITY - Abdurashidovna, Mukhitdinova Firyuza; Duisebaevna, Kutybaevа Elizavettа; Aitmuratovich, Daumenov Berdakh; Dilfuza, Ismailova (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the issues of criminal and family violence against women, formulates suggestions for improving national legislation in this area.The author has studied international regulatory documents as well as foreign experience and tools for the prevention of criminal violence against women, the laws of the Uzbek Republic, as well as a number of foreign countries; The degree of influence of these documents on national legislation and law enforcement practice is assessed.The importance of the institution of the family in society determines the value of family law, however, the question of the place of family law in the system of branches of law for a long time remains debatable. The term "family law" is understood as a science, as a branch of law, and as a branch of legislation. In our opinion, no matter what positions are taken by certain authors who study these issues, family law has a determining role in regulating the relations of the individual, family, society, and the state. "Family law as a science, branch of law, legislation are United by one goal, this includes: establishing a reasonable balance between the interests of the individual, family, society; state regulation of family relations, protection of the rights of family members or persons standing on the threshold of its education; protection of the rights of the child."